Pengaruh Diskon, Promosi dan Kualitas Pelayanan terhadap Keputusan Pembelian Online dengan Menggunakan Aplikasi Alfagift - AZ, Siti Marlina; Ratna, Ratna; Fithoni, Ahmad; Delima, Rts. Hartha (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This research aims to determine the influence of discounts, promotions and service quality on purchasing decisions using the Alfagift application in Muara Bulian. The analysis used is quantitative analysis using validity and reliability tests, multiple linear regression analysis, t test, F test and coefficient of determination (R2). The research results show that simultaneously there is a significant influence between the discount, promotion and service quality variables on online purchasing decisions using the Alfagift application, but partially only the discount variable does not have a significant influence on online purchasing decisions using the Alfagift application in Muara Bulian.